RAIN ENERGY AS A GREEN ENERGY SOURCE? - Andrej Predin; Gorazd Hren (Journal of Energy Technology, 2024)
This paper focuses on using rain as a potential energy source in areas of monsoon rain. On the basis of physical considerations, taking into account the basic laws of mechanics, fluid mechanics and aero-dynamics, the idea of exploiting rain as a green source for energy production is developed. The energy-poor areas of Asia could take advantage of heavy rain during periods of monsoons. From the commercial point of view, this energy source is not profitable, but bearing in mind the underdevelopment of those areas, this energy source could be sufficient for the primary energy supply of individual residential houses.